The Influence Of Literacy Support On Reading, Science, Mathematics And ICT Literacy Performance Among Form Four Students In Peninsular Malaysia - Ganasan, Marcia Jane (2018)
The study aims to examine students’ literacy performance levels, knowledge and cognitive skills and performance differences in the states of Penang, Perak, Perlis, Kedah, Selangor, Kelantan, Terengganu and Johor. The eight states that participated in this study represent the North zone (Penang, Perak, Perlis and Kedah), South zone (Johor), Central zone (Selangor) and the East zone (Kelantan and Terengganu) of Malaysia. The domains of reading, science, mathematics and ICT are integrated as subjects that provide a holistic discipline to explore students’ abilities and literacy levels across the states.